2015
DOI: 10.1371/journal.pone.0116722
|View full text |Cite
|
Sign up to set email alerts
|

Rift Valley Fever Virus Infection in Golden Syrian Hamsters

Abstract: Rift Valley fever virus (RVFV) is a formidable pathogen that causes severe disease and abortion in a variety of livestock species and a range of disease in humans that includes hemorrhagic fever, fulminant hepatitis, encephalitis and blindness. The natural transmission cycle involves mosquito vectors, but exposure can also occur through contact with infected fluids and tissues. The lack of approved antiviral therapies and vaccines for human use underlies the importance of small animal models for proof-of-conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Consistent with previous work in animal models with the pathogenic ZH501 strain of RVFV [ 7 , 8 , 9 , 13 , 24 , 25 , 26 ], our study found that a variety of tissues are able to support RVFV MP-12 replication in the STAT2 KO hamsters, demonstrating the ability of the virus to cause systemic infection and lethal disease in this model. Notably, however, previous studies with BALB/c mice, Lewis rats, and rhesus macaques challenged with aerosolized RVFV found substantial levels of viremia [ 9 , 13 , 26 ], whereas we found that only two hamsters that were moribund at the time of sacrifice, had detectable low-level viremia.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous work in animal models with the pathogenic ZH501 strain of RVFV [ 7 , 8 , 9 , 13 , 24 , 25 , 26 ], our study found that a variety of tissues are able to support RVFV MP-12 replication in the STAT2 KO hamsters, demonstrating the ability of the virus to cause systemic infection and lethal disease in this model. Notably, however, previous studies with BALB/c mice, Lewis rats, and rhesus macaques challenged with aerosolized RVFV found substantial levels of viremia [ 9 , 13 , 26 ], whereas we found that only two hamsters that were moribund at the time of sacrifice, had detectable low-level viremia.…”
Section: Discussionsupporting
confidence: 92%
“…The infection of RVFV in Syrian hamsters has been well-described (91). The study results have assessed the susceptibility of Syrian hamsters to RVFV infection and shown that viral infection results in viremia, elevation of viral loads in liver, brain, and spleen tissues, observation of severe hepatocellular necrosis in the early stage of infection, and intense immunoreactivity of affected hepatocytes (27, 92, 93). Furthermore, using Syrian hamsters, Scharton et al proved that prophylactic Favipiravir (T-705) can effectively protect infected individuals against RVFV infection and reduce delayed-onset neurologic disease observed with ribavirin treatment (94).…”
Section: Syrian Hamster Used For Research In Viral Infectionsmentioning
confidence: 99%
“…An alternative rodent model are Golden Syrian hamsters, which are susceptible to RVFV and Hantaviruses. When devoid of functional STAT‐2, they are also highly susceptible to SFTSV, showing thrombocytopenia, typical marked systemic inflammation, and mortality …”
Section: Replication Cyclementioning
confidence: 99%